Low Vitamin D Status Predicts Poor Clinical Outcome in Advanced Melanoma Treated With Immune Checkpoint or BRAF/MEK Inhibitors: A Prospective Non-Interventional Side-by-Side Analysis - Reichrath, Jörg; Biersack, Florian; Wagenpfeil, Stefan; Schöpe, Jakob; Pföhler, Claudia; Saternus, Roman; Vogt, Thomas (Frontiers in Oncology, 2022)
In melanoma and other malignancies, low vitamin D status is associated with increased risk and poor prognosis. However, there are limited data of the impact of 25(OH)D serum concentration (s.c.) on clinical outcome in advanced melanoma. We tested hypothesis that vitamin D status is predictive of efficacy and safety in patients treated for metastasized melanoma with BRAF-, MEK-, CTLA-4-, and/or PD-1-inhibitors. Severe vitamin D deficiency (defined as 25(OH)D s.c. < 10 ng/ml) was associated with markedly reduced overall (OS) and progress-free (PFS) survival, with increased tumor-load (TL, measured as s.c. of S100 protein or lactate dehydrogenase (LDH)), and with a trend for lower frequency of adverse events (AEs). An increase in average 25(OH)D s.c. of 1 ng/ml was associated with a 3.9% reduced risk for progressive disease (HR=0.961, p=0.044), with a reduction of LDH s.c. of 3.86 U/l (p=0.034, indicating a reduction of TL), and with a trend for reduced frequency of AEs (AE ratio -0.005; p=0.295). Patients with average 25(OH)D s.c. >/= 10 ng/ml and BRAF-mutant melanoma showed a trend for a higher frequency of AEs, as compared to individuals with BRAF wild type melanomas. Our data indicate that vitamin D deficiency is associated with poor clinical outcome in patients treated for metastasized melanoma with BRAF/MEK inhibitors or immunotherapy. Although it needs to be proven in future interventional trials whether optimizing serum 25(OH)D improves clinical outcome in these patients, we recommend that 25(OH)D s.c. should be analyzed and vitamin D deficiency treated in all patients with advanced melanoma.